TEST PROGRAMS AS MEAN OF REALIZATION OF THE DIFFERENTIATED GOING NEAR CONTROL OF Y OF CORRECTION OF EDUCATIONAL ACHIEVEMENTS OF STUDENT - Kolechinceva, T. (Journal of Information Technologies in Education (ITE), 2010)
In the article the necessity of introduction of the differentiated going is grounded near control of educational achievements of student and computer support of this process.